Electrochemical Performance of Ba0.5Sr0.5Co0.8Fe0.2O3−δ in Symmetric Cells With Sm0.2Ce0.8O1.9 Electrolyte for Nitric Oxide Reduction Reaction - Shi, Huangang; Chu, Guowei; Tan, Wenyi; Su, Chao (Frontiers in Chemistry, 2020)
The emission of nitric oxide from the combustion process of fossil fuels causes air pollution problems. In addition to traditional removal methods, nitric oxide can be removed by the electrochemical reduction method. In this study, Ba0.5Sr0.5Co0.8Fe0.2O3-δ powders were synthesized using a solid-state reaction method. Symmetrical cells, with Sm0.2Ce0.8O1.9 as the electrolyte and Ba0.5Sr0.5Co0.8Fe0.2O3-δ as the electrodes, were prepared as the electrochemical reactor for nitric oxide reduction. In the process of electrochemical reduction, nitric oxide reduction occurs at the cathode and oxygen evolution occurs at the anode. To study the nitric oxide reduction performance of the electrode, impedances of the symmetrical cell in different atmospheres were analyzed. For the nitric oxide conversion in symmetric cells, two different modes, dual chamber and single chamber, were applied. Results demonstrated that the denitrification performance of the double chamber was better but the single chamber mode had other advantages in its simple structure. Preliminary stability results of the single chamber symmetric cell show that the electrochemical reduction of nitric oxide in symmetric cells with BSCF performed most reliably.